Unsalable Vegetables Ensiled With Sorghum Promote Heterofermentative Lactic Acid Bacteria and Improve in vitro Rumen Fermentation - Forwood, Daniel L.; Holman, Devin B.; Chaves, Alex V.; Meale, Sarah J. (Frontiers in Microbiology, 2022)
This study characterized the nutritive and microbial profiles, and fermentation characteristics of silage comprising: (1) 100% dry-matter (DM) sorghum; (2) 70% sorghum + 30% DM carrot or pumpkin and (3) 40% sorghum + 60% DM carrot or pumpkin, with or without a probiotic inoculant. After 70 d ensiling, silage was incubated for 48 h using the in vitro batch culture technique. Crude protein and non-fiber carbohydrates in silage increased (P ≤ 0.01) by 5.7 percent point (pp) and 9.6 pp with 60% DM pumpkin, respectively. The V4 region of the 16S rRNA gene was sequenced to profile pre-ensiled and ensiled archaeal and bacterial communities. Silages containing carrot or pumpkin strongly influenced microbial structure (PERMANOVA: R2 = 0.75; P < 0.001), despite ensiled treatments being dominated by Lactobacillus, except the control, which was dominated by Weissella and Pediococcus (P < 0.01). Linear discriminant analysis indicated that carrot and pumpkin silages were responsible for increased relative abundance of Lactobacillus and Acinetobacter (log LDA score ≥ 2), respectively. After 48 h incubation, carrot and pumpkin inclusion increased (P < 0.01) in vitro dry matter digestibility by 22.5 and 31.3%, increased total volatile fatty acids VFAs by 16 and 20.6% (P < 0.01) and tended (P = 0.07) to increase gas production, respectively. Therefore, this study supports the use of carrot or pumpkin in sorghum silages to maximize feed digestibility and total VFA concentrations.